Incremento de la productividad para mejorar los niveles de competitividad del arroz del recinto La Cleotilde del cantón Baba de la provincia de Los Ríos, mediante la asociación de los pequeños productores - García Rizzo, Carlos Benito (2013)
The present research project whose title bears the name: increase of productivity to improve the levels of competitiveness of the rice of the enclosure the Cleotilde of the Canton Baba of the province of the Ríos, through the Association of small producers; He was pleased to do the graduate of the Faculty of economic sciences Mr. Carlos Benito García Rizzo to well-known people, relatives and friends of the place. Having extracted relevant points regarding lands, applications, media and follow to become subjects of aid; Thus also established forms and amounts production of the same, are established weaknesses, themes and main point, from which it would seek to improve them. Approaches are performed with MAGAP people, who guided and exposed guideline to of funding for the implementation of this project through the BNF……